New Strategies in the New Millennium: Servant Leadership As Enhancer of Service Climate and Customer Service Performance - Linuesa-Langreo, Jorge; Ruiz-Palomino, Pablo; Elche-Hortelano, Dioni (Frontiers in Psychology, 2017)
In a world in which customers are increasingly looking for solutions to their own concerns on how to make a better globalized world, new organizational strategies are emerging to approach the customer in the current third millenium. Servant leadership, which involves to put employees’ needs first and serve the broader society, is emerging as a new strategic mechanism to approach the customer in line with the new social values-driven Marketing 3.0 era. Yet research has ignored the role and the various mechanisms servant leadership might utilize to improve customer service performance of their service units. Spanning 185 hotels located in Spain, a sample of 247 service units –in close contact with customers– was used to investigate whether servant leadership enhances customer service performance through shaping a service climate within the service unit. Results revealed that service climate mediates the positive influence of servant leadership on customer service performance. Managers can use these findings to note the value of leading the service unit in a servant friendly direction which is better aligned with the new aspirations of customers, today.